Strengthening Social-Resilience in Settlements; Creating A Resilient Model Village Brunei - Denis, TWINOMUGISHA; Adenan, Rozia Haji; Ismail, Zulkefle (MAJ - Malaysia Architectural Journal, 2025)
This research proposal aims to investigate and develop a comprehensive strategy for enhancing social resilience within settlements, with a specific focus on creating a resilient model village in Brunei. The study will employ a multidisciplinary approach, blending qualitative and quantitative methodologies, to understand the socio-cultural dynamics, community networks, and adaptive capacities within Brunei's settlements. Through extensive community engagement and participatory research methods, the project will identify both the vulnerabilities and strengths of local social structures and traditions, emphasizing the incorporation of indigenous knowledge systems. By examining the impact of external stressors on social cohesion and employing a community-driven approach, this research seeks to develop a framework that integrates traditional practices with contemporary resilience-building strategies. Through partnerships with local stakeholders, including community leaders, governmental bodies, and non-governmental organizations, the study aims to co-create solutions that foster community cohesion, strengthen social networks, and enhance adaptive capacities. Additionally, the research will focus on evaluating the feasibility and effectiveness of implementing a resilient model village concept as a means to highlight practical strategies for bolstering social resilience within Brunei's settlements. This will help in the development of a replicable model that integrates local wisdom with modern approaches, providing valuable insights and actionable recommendations for policymakers, community leaders, and practitioners involved in fostering resilient settlements not only in Brunei but also in similar socio-cultural contexts globally.